2021
DOI: 10.1016/j.jiph.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of critical illness and mortality based on symptoms and initial physical examination for patients with SARS-CoV-2: A retrospective cohort study

Abstract: Introduction An unidentified cluster of pneumonia was identified in Wuhan city of China in the last week of December 2019, named Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2). The current study explored the predictors associated with critical illness and mortality based on symptoms at the time of admission and initial physical examination findings in patients with SARS-CoV-2. Material and methods A total of 249 records of laboratory-confirmed SARS-COV-2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Our findings were different from the study by Chauhan et al 5 that showed more proportion of fever, fatigue, myalgia, abdominal pain in those who died as compared to those who survived. However, the study by Bairwa et al 6 concurred with the clinical symptomatology of our study. The case fatality rate of our cohort was 19.5% which was similar to that in multiple other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were different from the study by Chauhan et al 5 that showed more proportion of fever, fatigue, myalgia, abdominal pain in those who died as compared to those who survived. However, the study by Bairwa et al 6 concurred with the clinical symptomatology of our study. The case fatality rate of our cohort was 19.5% which was similar to that in multiple other studies.…”
Section: Discussionsupporting
confidence: 93%
“…However, the study by Bairwa et al . [ 7 ] concurred with the clinical symptomatology of our study. The case-fatality rate of our cohort was 19.5% which was similar to that in multiple other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The case-fatality rate of our cohort was 19.5% which was similar to that in multiple other studies. [ 6 7 8 9 10 ] Another cohort from our center during the “first wave” of the pandemic reported a case-fatality rate of 1.4%. [ 11 ] However, a study from a tertiary care hospital in New Delhi reported a CFR of 28.3%.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 20 An SpO 2 value ≤ 94% at the time of admission was also associated with higher odds of mortality; similar results were found in other studies as well. 9 , 17 , 21 We found a strong association between difficulty breathing at the time of admission and mortality, although the presence of a cough and fever was not significantly associated. Most of the studies conducted across different settings found a positive association between breathlessness at the time of admission and mortality 8 , 16 , 17 , 21 ; however, evidence regarding cough is conflicting.…”
Section: Discussionmentioning
confidence: 60%